Modulation of immunological activity on macrophages induced by diazinon. (15th March 2017) - Ogasawara, Nanako; Matsushima, Miyoko; Kawamura, Nami; Atsumi, Kazuko; Yamaguchi, Takehiro; Ochi, Haruka; Kusatsugu, Yuto; Oyabu, Sayaka; Hashimoto, Naozumi; Hasegawa, Yoshinori; Ueyama, Jun; Kawabe, Tsutomu
Abstract: Diazinon is an organophosphorus (OP) insecticide and is widely used not only in agriculture but also homes and garden in Japan. Diazinon has been reported to increase TNF-α production in rat serum and brain, suggesting that it can modify the proinflammatory response. In this study, we investigated the effects of diazinon on macrophage functions, such as cytokine production, reactive oxygen species (ROS) generation, cyclooxygenase (COX)-2 and inducible nitric oxide synthase (iNOS) expressions, cell-surface molecule expressions, and phagocytosis in RAW264.7 cells. In RAW264.7 cells, diazinon induced the production of TNF-α and IL-6. Diazinon induced ROS generation and the expressions of COX-2, iNOS, and cell-surface molecules CD40, CD86, and MHC class II, but reduced phagocytic activity in RAW264.7 cells. ERK and p38, but not JNK and p65 were involved in diazinon-induced IL-6 expression in RAW264.7 cells. We also examined these proinflammatory responses in bone marrow-derived macrophages (BMDM) and bronchoalveolar lavage fluid (BALF) cells. These results suggested that diazinon can activate macrophages and enhance inflammatory responses.